Adult Siblings Consider the Future: Emergent Themes. Issue 3 (26th March 2015) - Davys, Deborah; Mitchell, Duncan; Haigh, Carol
Abstract : Background: This study aimed to explore the perceptions of adult siblings regarding a future care role and compare with perceived parental wishes as family often provide a key support role in the lives of people who have an intellectual disability. Materials and Method: Semi‐structured interviews were undertaken with 15 adult siblings and an approach aligned to IPA was used to analyse the results. Results: Emergent themes demonstrated that intellectual disability has an impact upon sibling lives yet the degree and range of impact varies. Most participants were concerned about the future, service issues were raised as was futures planning, siblings' needs, the positive impact of intellectual disability and influence of life stage upon care giving. Conclusion: The findings highlight that whilst the impact of intellectual disability upon adult siblings is variable, siblings are concerned about the future, and that life stage and circumstance appear to influence care giving.